Attack of the Scraplets! - Paz, Veronica (New York : Little, Brown and Co., 2012)
Optimus Prime and Arcee discover a horde of alien robots, the Scraplets, with razor-sharp teeth and a love for chomping on fresh metal.
"Based on the episode 'Scrapheap' written by Marsha Griffin."
Keywords: Transformers (Fictitious characters) - Juvenile literature; Robots - Juvenile literature; Science fiction